Diagnostic significance of interleukin levels in blood serum in premenopausal women with chronic endometritis and normal weight or overweight - K. D. Ievleva; I. N. Danusevich; A. V. Atalyan; I. Yu. Egorova; N. I. Babaeva; M. A. Rashidova; M. R. Akhmedzyanova; L. F. Sholokhov; I. G. Nadeliaeva; L. M. Lazareva; L. V. Suturina (Acta Biomedica Scientifica, 2024)
Background. Chronic endometritis (CE) is an inflammatory hysteropathy causing miscarriage and infertility. High invasiveness of the main method of CE diagnosis and vague clinical picture necessitate the need for the development of less invasive approaches to establish the presence of this disease.The aim of the study. To establish a significant association of the concentration of pro- and anti-inflammatory interleukins in the blood serum with the presence of chronic endometritis in premenopausal women without concomitant endocrine diseases.Materials and methods. This re-analysis of the data is based on the results of a cross-sectional study conducted between May 2017 and December 2019 which included 198 premenopausal women. In all participants, body weight and height were measured with the calculation of the body mass index, the concentration of Creactive protein, pro- and anti-inflammatory cytokines in the blood serum was determined, and a pipelle biopsy was performed to determine the CD138 expression in the endometrial stroma. Non-parametric methods, as well as ROC analysis, were used for statistical analysis.Results. 86 women were included in the re-analysis of the data, 37 of them had a confirmed diagnosis of chronic endometritis. Statistically significantly higher values of interleukin 1 (IL-1) concentration (p = 0.0028) and IL-1/tumor necrosis factor α ratio (p < 0.001) were determined in women with CE and normal body weight; threshold values of these parameters were ≥ 1.35 pg/ml (sensitivity 75 %, specificity 83 %; 95% confidence interval (95% CI): 0.88–2.15) and ≥ 1.03 (sensitivity 85 %, specificity 78 %; 95% CI: 0.81–1.27) respectively. Such a relationship was not revealed in women with overweight.Conclusions. The obtained results can be the basis for conducting a larger-scale study with determining the concentration of cytokines not only in the blood serum, but also in the endometrium of women with CE, which will allow the development of a minimally invasive method for determining the risk of the presence of chronic endometritis in premenopausal women.